Lionel in the spring - Krensky, Stephen; Natti, Susanna (New York : Dial Books for Young Readers, 1990)
Lionel's spring activities include plans to plant a vegetable garden, helping celebrate his parent's anniversary, playing with his friend, and participating in spring cleaning.
1 13
Keywords: Spring -- Fiction; Family life -- Fiction